Сутність та особливості кадрового забезпечення Державної митної служби України - Музичук, О. М.; Muzychuk, O. M.; Невядовський, В. О.; Neviadovskyi, V. O.; Завальний, М. В.; Zavalnyi, M. V.; Vladyslav Neviadovskyi (Вісник Пенітенціарної асоціації України. - 2023. - № 3. - С. 69-76, 2023)
У статті наголошено на тому, що повномасштабне російське вторгнення призвело до перебудови та переосмислення концепції діяльності Державної митної служби України. Зазначено, що саме своєчасна та злагоджена перебудова кадрового забезпечення відіграла провідну роль в адаптації діяльності Державної митної служби України до нових викликів воєнного стану. Акцентовано увагу на тому, що особливості кадрового забезпечення Державної митної служби України є невіддільними від тих об’єктивно встановлених цифрових, науково-технічних, економічних умов, що визначають поточний стан діяльності та закладають перспективи розвитку вітчизняних органів публічної влади.

The article emphasizes that the full-scale Russian invasion led to the restructuring and rethinking of the concept of the State Customs Service of Ukraine. In the conditions of the war, a decision was made to evacuate the personnel of the customs offices of the northern and eastern regions, to remove equipment for the preservation of databases and information resources. In such conditions, the personnel of the customs offices of the western and southern regions was strengthened at the expense of evacuated employees and transferred to a strengthened mode of round-the-clock work. It was noted that the timely and coordinated restructuring of personnel support played a leading role in adapting the activities of the State Customs Service of Ukraine to the new challenges of martial law. Attention is focused on the fact that the specifics of staffing of the State Customs Service of Ukraine are inseparable from those objectively established digital, scientific and technical, economic conditions that determine the current state of activity and lay the prospects for the development of domestic public authorities. It is claimed that the first such features, which have not yet been widely covered in the scientific literature, are ethical features that are actualized in the context of rethinking the requirements for public servants, their business and moral qualities. Ethical features of personnel support, among other things, are reduced to the formation of a culture of work with personnel, ensuring high respect for each individual employee of the enterprise, institution or organization on the part of employees of personnel departments, as well as the implementation of the service model of personnel work. It is substantiated that the second group of features of personnel support of the State Customs Service of Ukraine are innovative, technical and digital, which form a flexible approach to the development of employees, provide extended motivation for high indicators of professional activity, stimulate changes, etc.

В статье отмечено, что полномасштабное российское вторжение привело к перестройке и переосмыслению концепции деятельности Государственной таможенной службы Украины. Отмечено, что своевременная и слаженная перестройка кадрового обеспечения сыграла ведущую роль в адаптации деятельности Государственной таможенной службы Украины к новым вызовам военного положения. Акцентировано внимание на том, что особенности кадрового обеспечения Государственной таможенной службы Украины неотделимы от объективно установленных цифровых, научно-технических, экономических условий, которые определяют текущее состояние деятельности и закладывают перспективы развития отечественных органов публичной власти.
The essence and peculiarities of personnel support of the State Customs Service of Ukraine
Keywords: Державна митна служба України; кадрове забезпечення; адміністративно-правовий статус; воєнний стан; State Customs Service of Ukraine; personnel support; administrative and legal status; martial law; Государственная таможенная служба Украины; кадровое обеспечение; административно-правовой статус; военное положение